2012
DOI: 10.5194/acp-12-3939-2012
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the climate significance of halogen-driven ozone loss in the tropical marine troposphere

Abstract: Abstract.We have integrated observations of tropospheric ozone, very short-lived (VSL) halocarbons and reactive iodine and bromine species from a wide variety of tropical data sources with the global CAM-Chem chemistry-climate model and offline radiative transfer calculations to compute the contribution of halogen chemistry to ozone loss and associated radiative impact in the tropical marine troposphere. The inclusion of tropospheric halogen chemistry in CAM-Chem leads to an annually averaged depletion of arou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
198
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 167 publications
(216 citation statements)
references
References 60 publications
15
198
3
Order By: Relevance
“…Tropospheric ozone is a greenhouse gas and the primary source for OH radicals, which are an important sink for methane in the tropical atmosphere (38). Atmospheric models estimate that halogen-mediated ozone loss could deplete the tropospheric ozone column by 10% per year (18). These estimates are as of yet unconstrained by halogen radical observations in the FT and predict ∼0.02 ppt IO in the upper troposphere over the tropical Atlantic (18), which is a factor of five less IO than the upper limit reported for this region (28) and the FT-IO mixing ratio that we find over the Central Pacific ocean.…”
Section: Resultscontrasting
confidence: 38%
See 3 more Smart Citations
“…Tropospheric ozone is a greenhouse gas and the primary source for OH radicals, which are an important sink for methane in the tropical atmosphere (38). Atmospheric models estimate that halogen-mediated ozone loss could deplete the tropospheric ozone column by 10% per year (18). These estimates are as of yet unconstrained by halogen radical observations in the FT and predict ∼0.02 ppt IO in the upper troposphere over the tropical Atlantic (18), which is a factor of five less IO than the upper limit reported for this region (28) and the FT-IO mixing ratio that we find over the Central Pacific ocean.…”
Section: Resultscontrasting
confidence: 38%
“…Atmospheric models estimate that halogen-mediated ozone loss could deplete the tropospheric ozone column by 10% per year (18). These estimates are as of yet unconstrained by halogen radical observations in the FT and predict ∼0.02 ppt IO in the upper troposphere over the tropical Atlantic (18), which is a factor of five less IO than the upper limit reported for this region (28) and the FT-IO mixing ratio that we find over the Central Pacific ocean. The possibility of iodine recycling from aerosols could further extend the effective iodine lifetime and add an additional ozone loss pathway that is not yet considered in atmospheric models.…”
Section: Resultscontrasting
confidence: 38%
See 2 more Smart Citations
“…The most recent estimates indicate that between 2 and 8 parts per trillion by volume (pptv) of VSL Br are injected to the stratosphere [World Meteorological Organization (WMO), 2014]. In the case of iodine, the oceans provide the main source of iodine compounds to the atmosphere [Carpenter et al, 2013;Saiz-Lopez et al, 2012a] where they reduce the global warming effect of ozone in the marine troposphere [Saiz-Lopez et al, 2012b]. Recent studies have reported values of 0.2-0.4 pptv of iodine monoxide (IO) in the free troposphere over the subtropical station of Izaña in the Atlantic Ocean (Canary Islands) [Puentedura et al, 2012] and 0.1-0.2 pptv range throughout the tropical free troposphere of the Pacific Ocean , demonstrating the ubiquitous presence of the radical in the marine free troposphere.…”
Section: Introductionmentioning
confidence: 99%